Spread-Spectrum Watermarking of Audio Signals - Kirovski, Darko; Malvar, Henrique S. (IEEE Transactions on Signal Processing, 2003)
Watermarking has become a technology of choice for a broad range of multimedia copyright protection applications. Watermarks have also been used to embed format-independent metadata in audio/video signals in a way that is robust to common editing. In this paper, we present several novel mechanisms for effective encoding and detection of direct-sequence spread-spectrum watermarks in audio signals. The developed techniques aim at i) improving detection convergence and robustness, ii) improving watermark imperceptiveness, iii) preventing desynchronization attacks, iv) alleviating estimation/removal attacks, and finally, v) establishing covert communication over a public audio channel. We explore the security implications of the developed mechanisms and review watermark robustness on a benchmark suite that includes a combination of audio processing primitives including: time- and frequency-scaling with wow-and-flutter, additive and multiplicative noise, resampling, requantization, noise reduction, and filtering.